Comportamento do capim-vetiver (Chrysopogon zizanioides (L.) Roberty) como contribuição na estabilização de talude da margem Rio São Francisco - Machado, Lorena (2014)
The changes in the hydrological regime in the São Francisco River basin, due to the implementation of hydroelectric power dams, are causing low water levels and therefore the bank erosion promoted by the riverbank undercutting. These changes, along with deforestation of riparian vegetation require economically viable and efficient measures since been affecting the population of the Lower São Francisco. The objective of this study was to evaluate the behavior of the root system of vetiver grass (Chrysopogon zizanioides) in ordet o evaluate its ability to restructuring physical soil mechanics and suitability to the process of stabilization of erosion of banks, as well as evaluate its effect on the soil penetration resistance (PR). To evaluate the influence of the grass on soil shear strength Root Density (RL), the Root Length Density (RLD), the Root Area Ratio (RAR), the Root Tensile Strength (TR) and the Root Cohesion (CR) were measured. The results were subjected to analysis of variance (p <0.05) using the SISVAR and then was held the polynomial regression analysis. To evaluate the RP, sampling was carried out near vetiver grass cultivation and the rows between crops along the profile until a depth of 0.60 m. The soil water was determined by weighing method, the RP by an automated penetrometer, the particle-size analysis by densitometry and root density by the monolith method. The results of RP, moisture and root density were subjected to analysis of variance (p <0.05) and afterwards the means were compared by Tukey test using the software SISVAR. For DR, DCR and RAR layer 0-0.10 m showed higher results which yielded 4.84 kg m-3, 12.45 km m-3, 1.66%, respectively. While the average result of TR was 83 MPa and CR 528 kPa. The vetiver grass near points had a mean RP of 1793.94 kPa and average soil water of 11.78%, differing from the sampled points in the rows between crops. The PR and soil moisture were not statistically different throughout the depths. The vetiver grass promoted ground cover, favoring a higher water retention and consequently decreasing the RP, as well as helping to increase the soil shear strength, giving a very important contribution to slope stabilization.